Pengujian Sistem Informasi Aplikasi Perpustakaan basis Website Menggunakan White Box Testing - Atina Fahma Rosyada; Ikhwan Sukirman Ikhwan Sukirman; Muhammad Afrizal Nur; Kristiawan Kristiawan; Aries Saifudin (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The use of book lending applications in the library is a useful tool to make it easier for borrowers to borrow books, which are usually obtained manually through notes. Library managers can simplify the collection of books and borrowers by utilizing this system. ensure that book lending access is managed properly, the admin can manage it. In addition to knowing what might happen when the system is running, the white box testing method is used to find out how the system works structurally. Similar to Cyclomatic Complexity, the system worked well during white box testing on the user login page. White Box Testing, which is a test method that uses a control structure and procedural design, is one of many testing methods. The findings of this study are useful for understanding the application system after the implementation stage. White Box Testing is one such testing method. White Box testing has evolved into system testing that can provide specifics about programming source code, algorithm paths, and paths. After passing this white box method, the second testing stage is carried out because the program will not run if the logic or algorithm flow is wrong. Applications that have been developed so that they can be presented in a perfect system level according to how they work and can be useful for users are tested using the findings of this study.